Refiguring Motherhood Beyond Biology - Renegar, Valerie; Cole, Kirsti (Interdisciplinary Research in Motherhood, 2023)
This book unpacks and interrogates dominant constructions of mothering, making use of interdisciplinary, ideological and theoretical perspectives to investigate how new rhetorics of mothering can expand the realm of maternal care-givers beyond the biological definitions of motherhood. This diverse collection is at the cutting-edge of rhetoric, feminism, and motherhood studies, and the chapters challenge the confines of biological parenting as heteronormative within the neo-liberal nuclear family. The contributors examine, how despite the diversity of parental relationships, many are excluded by the understanding of mothers biologically tied to their children. The volume seeks to expose the underpinnings of biological primacy and argues that 21st-century families and familial circumstances are ill-served by biological ideology. Topics include Re-Imagining Queer Black Motherhood, Chicana Feminist approaches to reproductive justice, the commercialization and medicalization of infertility, and ableism and motherhood. This is a unique and fascinating book suitable for students and scholars in gender studies, sexuality studies, communication studies, sociology, and cultural studies.